PERJANJIAN DAN PERBUATAN MELAWAN HUKUM DALAM PERJANJIAN - Edwin Yuliska (Normative Jurnal Ilmiah Hukum, 2020)
In general, an agreement can be made freely, free to enter into an agreement with anyone, free to determine its form or terms, and free to determine its form, that is, written or unwritten. An agreement that is legally made can be canceled within the agreement period and the consequences of the cancellation of the agreement, first of all it must be seen whether in the agreement there is a clause governing the possibility of canceling the agreement along with the causes and consequences for the parties. Binding Deed of Sale and Purchase is an authentic deed that has the strength of proof. This is intended by the parties to provide more protection and legal certainty for the parties that make it. If the matters agreed upon in the sale and purchase agreement are violated or not fulfilled by the parties that made them, then it can be said that there has been a default.